Long‐term shifts in feedbacks among glacier surface change, melt generation and runoff, McMurdo Dry Valleys, Antarctica. Issue 8 (20th August 2021) - Bergstrom, Anna; Gooseff, Michael; Fountain, Andrew; Hoffman, Matthew
Abstract: Glaciers of the McMurdo dry valleys (MDVs) Antarctica are the main source of streamflow in this polar desert. Because summer air temperatures hover near 0°C small changes in the energy balance strongly affect meltwater generation. Here we demonstrate that increased surface roughness, which alters the turbulent transfer of energy between the ice surface and atmosphere, yields a detectable increase in meltwater runoff. At low elevations on the glaciers, basin‐like topography became significantly rougher over 13 years between repeat lidar surveys, yielding greater melt. In contrast, the smoother ice at higher elevation exhibited no detectable change in roughness. We pose a conceptual model of the cycle of glacier surface change as a result of climate forcing whereby glacier surfaces transition from being dominated by sublimation to becoming increasingly melt‐dominated, which is reversible under prolonged cool periods. This research advances our understanding of warm season effects on polar glaciers. Abstract : Analysis of repeat lidar coupled with long term records indicates a roughening glacier surface in response to recent warm events. This is causing increased meltwater generation and delivery to the downstream ecosystem. We present a conceptual model of cold‐based glacier surface evolution, which can be used as a basis for interrogating climate change impacts in other polar systems.